Christian Social Justice as the Direction for the Development of a Friendly to Life Environment - Biały, Stanisław (Studia Ecologiae et Bioethicae, 2004)
Justice (perfection) of a democratic law-abiding State expressed as an environment of social life: this is an issue, that very frequently is present upon the lips of jurists, politicians, political scientists, legislature members, but also: ethicists, bioethicists, moralists, theologians, and others. This subject has been also taken for reflection because of the fact, that we are living in such a system, and more: we must struggle with many problems, which make one ask: is the democratic system that is being constructed founded on sufficiently healthy foundations, so that it may be possible to say that we are all equal in relation to the law being passed and that its principles are just? So we have taken up here an ethical reflection on the subject of the philosophy of law and State (that is: philosophy of care for our life environment) predominant in the European Union, the directives of which, coming from different treaties and agreements, are being applied to our home legislature. The main axis, around which our reflections were developed, where the basic principles of the Christian concept of social justice. These are the basis for interpersonal and international dialogue. These principles are: «peace», «solidarity », «justice», «freedom », «truth» and «love». The main conclusion stemming from this article is: in the concept of State and law of today there is a lack of a permanent point of reference, and this point of reference should be the principle of social justice based on objective truth.